2021
DOI: 10.3389/fonc.2021.698572
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Therapeutic Value of Apolipoprotein A and a New Risk Scoring System Based on Apolipoprotein A and Adenosine Deaminase in Chronic Lymphocytic Leukemia

Abstract: Lipid metabolism is related to lymphomagenesis, and is a novel therapeutic target in some hematologic tumors. Apolipoprotein A (ApoA), the major protein of high-density lipoprotein (HDL), plays a crucial role in lipid transportation and protecting against cardiovascular disease, and takes effect on anti-inflammation and anti-oxidation. It is correlated with the prognosis of some solid tumors. Yet, there is no investigation involving the role of ApoA plays in chronic lymphocytic leukemia (CLL). Our retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The aberrant regulation of apo A could be attributed to CLL pathogenesis. Previous studies have provided clues to the mechanisms underlying the prognostic values of apo A and HDL-C ( 29 , 30 ). Proteolytic products of apo A participate in anti-angiogenic and anti-tumoral activities ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant regulation of apo A could be attributed to CLL pathogenesis. Previous studies have provided clues to the mechanisms underlying the prognostic values of apo A and HDL-C ( 29 , 30 ). Proteolytic products of apo A participate in anti-angiogenic and anti-tumoral activities ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein A (ApoA) is one of the main components of HDL. A low level of ApoA is related to the advanced stage of CLL patients [ 56 ]. ApoA1 mimetics could inhibit the proliferation of CLL cells.…”
Section: Intracelluar Metabolismmentioning
confidence: 99%
“…Recent studies have shown that increased serum levels of SIRT2 were associated with longer overall survival [ 5 ] whereas SIRT2 inhibitors induced cell death in leukemic cell lines [ 6 ]. Similarly, ADA, an enzyme of the purine metabolism related to lymphoid T cell differentiation and tumor cellular responses, has been found to be overexpressed in CLL patients and correlates with longer survival [ 7 ]. Another study showed that blockade of A2A adenosine receptors made CLL cells more susceptible to pharmacological treatments while restoring immune competence and T cell proliferation [ 8 ].…”
mentioning
confidence: 99%
“…1E ), a key protein involved in the control of autophagy flux and the NLRP3 inflammasome. These results suggest that the GRAMD1B locus might exert its biological function on CLL by modulating SIRT2, STAMBP, and ADA, which is a diagnostic biomarker for CLL that has been included in a new prognosis score designed to optimize the patient risk stratification [ 7 ].…”
mentioning
confidence: 99%